Will Your Students Choose to Be Physically Active?. Issue 7 (2nd September 2017) - Sibley, Benjamin A.
Abstract : Our goal as teachers should not just be to give our students a bag of tools that they may or may not use. Our goal should be to enable them to actually want to use those tools. This article explores the importance of autonomy-supportive teaching.